2016
DOI: 10.1021/acsnano.6b06559
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Role of Molecular Orbitals in Charge Transport through Individual Diarylethene Isomers

Abstract: Diarylethene molecules are prototype molecular switches with their two isomeric forms exhibiting strikingly different conductance, while maintaining similar length. We employed low-temperature scanning tunneling microscopy (STM) to resolve the energy and the spatial extend of the molecular orbitals of the open and closed isomers when lying on a Au(111) surface. We find an intriguing difference in the extension of the respective HOMOs and a peculiar energy splitting of the formerly degenerate LUMO of the open i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 38 publications
(82 reference statements)
3
37
0
Order By: Relevance
“…The techniques mostly rely on some form of metal-electrode breaking, such that a gap is formed of the proper size for bridging by a single molecule. The most widely employed methods are mechanically controllable break junctions [1][2][3] (MCBJ), modified scanning tunneling microscopes [4][5][6][7][8][9][10] (STM) or atomic force microscopes [11,12] (AFM), and bridges formed by electromigration of a nanofabricated metal wire. [13,14] When studies at cryogenic temperatures are required, as is needed to obtain sufficient resolution for resolving the electronic and vibrational structure of a molecule from differential conductance or shot noise measurements, STM and AFM techniques become very elaborate.…”
Section: Introductionmentioning
confidence: 99%
“…The techniques mostly rely on some form of metal-electrode breaking, such that a gap is formed of the proper size for bridging by a single molecule. The most widely employed methods are mechanically controllable break junctions [1][2][3] (MCBJ), modified scanning tunneling microscopes [4][5][6][7][8][9][10] (STM) or atomic force microscopes [11,12] (AFM), and bridges formed by electromigration of a nanofabricated metal wire. [13,14] When studies at cryogenic temperatures are required, as is needed to obtain sufficient resolution for resolving the electronic and vibrational structure of a molecule from differential conductance or shot noise measurements, STM and AFM techniques become very elaborate.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3b surface with the six lobes corresponding to its outer dpm ligands [61]. At this coverage there are neither preferred adsorption sites nor directional correlations with the herringbone reconstruction of the underlying gold substrate as it is the case for smaller molecules [63,64]. At lower coverage single molecules are found to preferably sitting on elbow sites of the herringbone reconstruction, however they can be easily displaced with the STM tip.…”
Section: Fe4h On Au(111)mentioning
confidence: 93%
“…(Figure 8g-h) and also performed conductance switching experiments and imaged dI/dV maps. [86] In a subsequent report on the same compound, the authors showed that the switching could be induced either by tunneling electrons or the electric field between the tip and surface. [87]…”
Section: Diarylethenes Under Uhvmentioning
confidence: 97%